Scontri tra spie agli inizi della guerra fredda l'Organisation Gehlen in Italia, 1946-1956 - Lias Ceide, Sarah (Clio.Saggi di scienze storiche, archeologiche e storico-artistiche, 2023)
Sarah Lias Ceide is a research associate at the German Historical Institute (DHI) in Rome. She received her PhD from the University of Naples Federico II within the doctoral program in Historical, Archeological and Artistic Sciences. Her research interests concentrate on German-Italian contemporary history, with a focus on Cold War Studies, Intelligence History, and the history of Italy's "Second Republic".